Effects and Moderators of Exercise on Sarcopenic Components in Sarcopenic Elderly: A Systematic Review and Meta-Analysis - Zhang, Yanjie; Zou, Liye; Chen, Si-Tong; Bae, Jun Hyun; Kim, Dae Young; Liu, Xiaolei; Song, Wook (Frontiers in Medicine, 2021)
Background: Sarcopenia is a muscle disease in loss of muscle strength, mass, and function associated with aging. Although protective effects of exercise on muscle mass and function are generally recognized, research findings in sarcopenic adults are inconsistent. It is necessary to conduct a systematic review to determine the effects of exercise on muscle strength, body composition, and physical performance in older adults with sarcopenia, and to examine the potential moderators including sociodemographic characteristics and exercise-related factors. Methods: Six electronical academic databases (Medline, Embase, CINAHL, Scopus, Cochrane Library, and SPORTDiscus) were used to retrieve the eligible studies from inception to May 2020. Two reviewers independently selected and extracted the data from each included study, and effect sizes were calculated by employing random-effect models with 95% confidential interval (CI). The Physiotherapy Evidence Database (PEDro) scale was used to assess study quality. Results: Seventeen studies (985 participants with sarcopenia, aged 67.6–86 years) were included in this review study. The meta-analytic results showed significant improvements in muscle strength [grip strength, SMD = 0.30, 95% CI (0.15, 0.45), I2 = 6%, p < 0.01; knee extension, SMD = 0.32, 95% CI (0.15, 0.50), I2 = 0%, p < 0.01; and chair and stand, SMD = 0.56, 95% CI (0.30, 0.81), I2 = 36%, p < 0.01], in physical performance [timed up and go, SMD = 0.74, 95% CI (0.48, 1.00), I2 = 0%, p < 0.01; and gait speed, SMD = 0.59, 95% CI (0.35, 0.82), I2 = 62%, p < 0.01], and in body composition [skeletal muscle mass index, SMD = 0.37, 95% CI (0.15, 0.58), I2 = 16%, p < 0.01; and appendicular skeletal muscle, SMD = 0.31, 95% CI (0.13, 0.49), I2 = 20%, p < 0.01]. However, there were no significant differences in other body composition (SMD = 0.20–0.36). Additionally, meta-regression revealed that the higher percent of female participants was significantly associated with improved gait speed (β = 0.0096, p = 0.03) and decreased skeletal muscle mass index (β = −0.0092, p = 0.01). Conclusions: The current meta-analysis suggests that exercise is a beneficial therapy, which has protective effects for older adults with sarcopenia. Some beneficial effects may be moderated by gender and exercise intensity.